2008
DOI: 10.1371/journal.pgen.0040009
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Population Study of Human Cell Lines Indicates that Dosage Compensation Is Virtually Complete

Abstract: X chromosome inactivation in female mammals results in dosage compensation of X-linked gene products between the sexes. In humans there is evidence that a substantial proportion of genes escape from silencing. We have carried out a large-scale analysis of gene expression in lymphoblastoid cell lines from four human populations to determine the extent to which escape from X chromosome inactivation disrupts dosage compensation. We conclude that dosage compensation is virtually complete. Overall expression from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
136
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 34 publications
11
136
0
1
Order By: Relevance
“…Of the other 26 genes, NLGN4X, PCDH11X, TBL1X, and TXLNG have functional Y-homologs, STS and KAL1 have pseudogene Y-homologs, and PLCXD1 is located in the Xp pseudo-autosomal region, all of which are features shared by many other genes that are known to escape XCI. In addition, 14 of these 31 genes were highlighted as potentially escaping XCI based on their consistently higher expression in females versus males ( Johnston et al 2008), and two were also previously identified as likely escaping XCI due to a lack of promoter methylation in females (Yasukochi et al 2010). We conclude that the use of comparative methylation profiling provides a powerful method for the classification of genes escaping XCI that is complementary to methods based on expression profiling.…”
Section: Discussionmentioning
confidence: 79%
“…Of the other 26 genes, NLGN4X, PCDH11X, TBL1X, and TXLNG have functional Y-homologs, STS and KAL1 have pseudogene Y-homologs, and PLCXD1 is located in the Xp pseudo-autosomal region, all of which are features shared by many other genes that are known to escape XCI. In addition, 14 of these 31 genes were highlighted as potentially escaping XCI based on their consistently higher expression in females versus males ( Johnston et al 2008), and two were also previously identified as likely escaping XCI due to a lack of promoter methylation in females (Yasukochi et al 2010). We conclude that the use of comparative methylation profiling provides a powerful method for the classification of genes escaping XCI that is complementary to methods based on expression profiling.…”
Section: Discussionmentioning
confidence: 79%
“…However, expression is not doubled in females, consistent with our RNA-seq data, in which ratios between BL6 and spretus reads were lower than 1, except for Xist, Mid1, and 6720401G13Rik. Similarly, human escape genes show a relatively modest increase in expression in female versus male cell lines, suggesting lower expression from the inactive X (Carrel and Willard 2005;Johnston et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…The reason for the incomplete inactivation of two genes (UBE2A and SAT1) is unclear. The degree of completion of XCI in adult tissues varies among studies depending on the tissue (Talebizadeh et al 2006), from 5.4% of X-linked genes with increased female expression in human lymphoblastoid cell lines (Johnston et al 2008) to 15-25% in fibroblasts and hybrid cells (Carrel & Willard 2005), and the distribution of genes that escape inactivation has been found not to be random along Sexual dimorphism in elongating bovine embryos the chromosome, but rather clustered and mapping primarily to the distal portion of the X chromosome short arm (Xp) (Miller & Willard 1998, Carrel & Willard 2005, far from the XIST gene (Huynh & Lee 2003). However, we could not establish a relation between linear distribution and escape from inactivation, which may be caused by the three-dimensional structure of the chromosome or by gene-specific regulation.…”
Section: Discussionmentioning
confidence: 99%